The Influencing Factors of Brand Loyalty and Brand Love - Isra Misra; Ali Sadikin; Aditya Achmad (Garuda Prestasi Nusantara Consulting, 2021)
Loving a brand can cause a positive feeling for the brand and want to use the brand for a long time. Research on the factors that make consumers feel love for a brand is still a little. This study aims to know at the factors that influence brand loyalty and brand love on iphone users in City in Souteast Asia. This research is a quantitative study using a quantitative descriptive approach. The analytical tool in this study is the Smart PLS (Path Analysis) application. The research variables consist of Romanticism (X1), Self Expression (X2), Hedonic Product (X3), Brand Loves (Y1) and Brand Loyalty (Y2) as mediating variables. Samples using the Yamane method with statistical probability methods amounted to 96 from all iphone users whose population is unknown. The results showed that romanticism, self expression and hedonic products directly have not been able to influence brand love and brand loyalty variables. However, with the presence of variable of mediator such as brand love, indirectly romanticism, self expression and hedonic products can influence brand loyalty variables with brand love as an intervening variable. Overall the results of this study are able to explain that intervening plays an important role become a mediator for other variables. Keywords : Romanticism, Self Expression, Hedonic Products, Brand Loves, and Brand Loyalty